(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Inappropriate antibiotic prescribing and usage in paediatric healthcare remains prevalent in Nepal, contributing to antimicrobial resistance. This cross-sectional observational study investigated antibiotic prescription patterns in government and private hospitals in Chitwan District and evaluated the efficacy of pharmacist-led parent counselling interventions. The study encompassed prescription pattern analysis and assessment of post-counselling outcomes, measuring changes in parental knowledge, attitudes, and practices (KAP) regarding antibiotic use. Results demonstrated distinct prescribing patterns between hospital types, with parental literacy correlating with private hospital preference. Post-intervention analysis revealed significant improvements in KAP scores (p < 0.05), particularly in private hospital settings, manifesting as enhanced antibiotic adherence and reduced inappropriate use. These findings suggest that pharmacist-led interventions effectively improve antibiotic stewardship and indicate the need for standardized prescribing protocols across healthcare sectors.